Improving Home Economics Students’ Interest in Biology: The Influence of Certain Effective Teachers’ Classroom Management Practices - Abeku Morgan, Messiah; Chrayoe Doku, Beatrice; Serwah Asare, Endurance; Dansoah, Janet; Kanamintie Nartey, John; Manteaw, Nelly (International Journal of Scientific Research and Management (IJSRM), 2023)
ABSTRACT            Studies have shown that teachers’ classroom management practices play a significant role in ensuring effective education and maintenance of students’ interest. Thus, the purpose of this study was to investigate the influence of students’ perceptions of some teachers’ Classroom Management Practices on their Interest in Biology. Students’ Interest in Biology (SIB) and Teacher Classroom management Practices (TCMP) questionnaires were used to collect data from 331 Biology students selected from seven schools from the New Juabeng Municipality of the Eastern Region of Ghana. Students’ interest in Biology was found to be generally moderate. Task orientation, equity and teacher support were often perceived. A positive moderate significant correlation between SIB and TCMP was also recorded. Task orientation and differentiation were found to be very good predictors of SIB. It was recommended that SHS Biology teachers should take steps to orient students well on tasks and use differentiated approaches in teaching.